Review of Cognitive Individual Differences in Second Language Acquisition - Xu Jared Liu (Australian Journal of Applied Linguistics)
Cognitive Individual Differences in Second Language Acquisition: Theories, Assessment and Pedagogy by Zhisheng Edward Wen, Richard L. Sparks, Adriana Biedroń, Mark Feng Teng, Walter de Gruyter, ISBN 978-1-61451-676-7.